2018
DOI: 10.1371/journal.pone.0205103
|View full text |Cite
|
Sign up to set email alerts
|

Fas/FasL pathway and cytokines in keratinocytes in atopic dermatitis – Manipulation by the electromagnetic field

Abstract: BackgroundAtopic dermatitis (AD) is one of the most frequent skin diseases. Changes of the keratinocytes functionality play a major role in the development of AD. For example, activation of the Fas (CD95)/FasL (CD178) pathway in AD does not lead to extensive apoptosis in skin. Binding of the Fas receptor to its protein ligand—FasL, which are present on the (AD)-modified keratinocytes, should result in the sequential induction of cell death, but there is no evidence of extensive apoptosis of these cells. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Thus, we presume that physcion may be beneficial to prevent and/or treat atopic diseases. Patients with AD possess higher levels of proinflammatory cytokines such as IL-6, TNF-α, IL-1β, IL-4, and IFN-γ [33,34,35]. Our results showed that physcion suppresses the levels of IL-6, TNF-α, IL-1β, IL-4, and IFN-γ, suggesting the potential of physcion in the treatment of AD.…”
Section: Discussionmentioning
confidence: 70%
“…Thus, we presume that physcion may be beneficial to prevent and/or treat atopic diseases. Patients with AD possess higher levels of proinflammatory cytokines such as IL-6, TNF-α, IL-1β, IL-4, and IFN-γ [33,34,35]. Our results showed that physcion suppresses the levels of IL-6, TNF-α, IL-1β, IL-4, and IFN-γ, suggesting the potential of physcion in the treatment of AD.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, TWEAK and TNF‐α co‐operate in the induction of keratinocyte apoptosis . Considering that TNF‐α is abundant in skin tissue of atopic dermatitis , our results explained the reduction of keratinocyte apoptosis in Fn14‐deficient skin of an atopic dermatitis model. We further elucidated that, as well as the anti‐inflammatory role, the inhibition of TWEAK/Fn14 interaction exerts its therapeutic effects by altering the TNFR1/TNFR2 expression profile, which may generate cell‐fate diversity of keratinocytes under different inflammatory contexts.…”
Section: Discussionmentioning
confidence: 52%
“…As well as these proinflammatory effects, extensive apoptosis of keratinocytes is one of the histological features in atopic dermatitis . We found that apoptotic cells decrease in skin lesions of Fn14‐deficient mice.…”
Section: Discussionmentioning
confidence: 63%
“…The interaction of the living organisms and EMF can occur via changes the activation of the channel and pumps in the cell membrane, so the cell ionic balance is rearranged [6]. EMF changes cell function via mainly oxidative stress biochemical cascades, intense apoptosis and other vital properties [7,8]. Reactive oxygen species (ROS) occurs in oxidative reactions to produce energy in metabolic and physiological processes in the organism.…”
Section: Discussionmentioning
confidence: 99%